P261 Primary care review of patients on long-term azithromycin for chronic lung conditions. (12th November 2019) - Tembo, T; Higgins, J; Mohammed, R; Greenhalgh, L; Francis, H; Ng Man Kwong, G
Abstract : Long-term Azithromycin (LTA) can be effective in reducing infective exacerbations of Chronic Obstructive Pulmonary Disease (COPD) and Bronchiectasis but has potential side effects affecting liver, prolonging the QT interval and hearing. 1 2 We aimed to identify current LTA prescribing and monitoring practices in primary care. Method: Retrospective study of patients with chronic lung conditions on LTA for a minimum of 6 months identified from primary care records. Results: Overall 40 patients on LTA were identified from a GP cluster group (7 practices covering population of approximately 50, 000) of whom 35 were suitable for inclusion. Average age 66 years (range 28–87 years, male 54%), COPD 18/35 (51%), Bronchiectasis 16/35 (46%) of whom 6/16 (38%) had an additional diagnosis of asthma. Mean duration on LTA was 4.5 years (range 1–12 years), 26/35 (74%) had LTA initiated in secondary care and the commonest dosing was 250 mg 3 times a week 25/35 (71%). Baseline sputum and ECG was obtained in only 16/35 (46%) respectively despite 12/35 (34%) having cardiac co-morbidities. Regular liver function tests (LFT) were performed in 32/35 (94%) but only 12/35 (34%) had hearing monitored. Potential drug interactions were identified in 12/35 (34%) patients. Where matched data was available (20 patients) the mean (median) 12 month pre- and post-LTA exacerbation rate was 5.4 (4.5) and 2.1(1.5) episodes respectively (P<<0.01). Conclusion: In our sample LTA appeared to reduce exacerbation rate with the majority of patients having LFT monitoring. However less than half had baseline ECG and sputum sampling and potential drug interactions were identified in one-third of patients. We therefore recommend reliable monitoring and follow-up of patients on LTA to reduce the risk of unfavourable side effects. References: British Thoracic Society. Guideline For Bronchiectasis In Adults. Thorax 2019;74 :S1. NICE ( 2018), National Institute for Health and Care Excellence, Clinical guideline NG115; Chronic obstructive pulmonary disease in overs 16s: diagnosis and management.